Influence of Ge content on the activity of Ru-Ge-B/Al2O 3 catalysts for selective hydrogenation of methyl oleate to oleyl alcohol - Sánchez, María Amparo (2013)
The influence of Ge content on the activity and selectivity of Ru-Ge-B/Al2O3 catalysts for the hydrogenation of methyl oleate to oleyl alcohol was studied. The results of catalyst characterization by TPR and XPS show that Ge is deposited on both the metal function aggregates and on the support surface. The fraction of Ge deposited on the metal function is in strong interaction with Ru, so that its metallic activity is significantly modified. Both dehydrogenating and hydrogenolytic activities of Ru are strongly diminished by Ge addition. The Ge/Ru = 2 is the optimum ratio for oleyl alcohol production.